The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/9926128
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Atomic Scale Interactions between RNA and DNA Aptamers with the TNF‐α Protein

Abstract: Interest in the design and manufacture of RNA and DNA aptamers as apta-biosensors for the early diagnosis of blood infections and other inflammatory conditions has increased considerably in recent years. The practical utility of these aptamers depends on the detailed knowledge about the putative interactions with their target proteins. Therefore, understanding the aptamer-protein interactions at the atomic scale can offer significant insights into the optimal apta-biosensor design. In this study, we consider o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…To investigate the interactions of both parameters with TNF-∗. In [ 15 ], calculations of binding free energy, molecular docking, and molecular dynamics simulations have been combined. On the other hand, exercise as a nonpharmacological strategy has been considered as a noninflammatory factor to reduce the complications of diabetes [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To investigate the interactions of both parameters with TNF-∗. In [ 15 ], calculations of binding free energy, molecular docking, and molecular dynamics simulations have been combined. On the other hand, exercise as a nonpharmacological strategy has been considered as a noninflammatory factor to reduce the complications of diabetes [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%